Post-Traumatic Stress Disorder (Ptsd) As Reflected in Toni Morrison’s Beloved - TAHULENDING, ESTER DIAN; OROH, ELISABETH Z.; RORIMPANDEY, RINNY S. (Program Studi Pendidikan Bahasa Inggris, 2024)
The aim of this research is to analyze the post-traumatic stress disorder experienced by the main character Sethe in the novel Beloved. Sethe experienced bad experiences in her past as a slave which ultimately monologues in the novel. This research is qualitative methods. The research analysis the novel the researcher use Sigmund Freud’s theory. Post-Traumatic Stress Disorder in a Beloved theory in the novel Beloved. The results of the research shows the presence, of anxiety, learned helplessness, horror, memories, and nightmares from post-traumatic stress disorder. The first is anxiety she felt that it was very dangerous out there. The anxiety that Sethe feels is because Sethe is not does not allow her daughter Denver to leave the house. Second, the feeling of helplessness experienced by Sethe, began when Sethe felt lonely, after losing her husband, mother, mother-in-law. The first horror experienced occurred when Buglar when he saw suddenly experienced by Sethe and her children were numerous, their house even shook itself, even trough there was no earthquake. Apart from that, Sethe also felt like she facing the incident again, thinking about memories, starting when Sethe answered a question from Paul D about what happened next when she tried to escape from the dirt. Sethe said was received harassment from the schoolteacher’s nephew and violence from the schoolteacher. For the second time, Sethe felt like she was facing the incident she experienced again. The nightmares begin when flashbacks from her past continue to haunt Sethe. Sethe’s bad experience made her trapped by traumatic thoughts in her past.